Hepatitis B virus replication in acute glomerulonephritis with chronic active hepatitis. Issue 6 (June 1985) - Cadrobbi, P; Bortolotti, F; Zacchello, G; Rinaldi, R; Armigliato, M; Realdi, G
Abstract : A 3 year old boy who had chronic active hepatitis type B with features of ongoing liver damage and active virus replication, developed acute membranous glomerulonephritis two years after the clinical onset of liver disease, when both hepatitis B e antigen and antibody were detectable in serum. After withdrawal of short term steroid treatment and resolution of hepatitis B virus replication, both glomerulonephritis and chronic hepatitis went into remission. Some months later hepatitis B surface antigen was no longer found in serum.